Manajemen Pengembangan Program Studi (Prodi) Studi Islam Program Pascasarjana (Pps) Universitas Islam Negeri (UIN) Rafen Fatah Palembang - ahmad zainuri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study examines the management of the development of the Postgraduate Program in Islamic Studies at UIN Raden Fatah Palembang Program which includes planning, implementation, and evaluation of accreditation as material in formulating a strategic plan (strategic plan), this study aims to describe the development management of the Master of Islamic Studies Program in PPs ) Raden Fatah State Islamic University (UIN) Palembang, both related to the planning of accreditation, implementation, and evaluation. Theoretically it is expected to be useful in adding intellectual property, especially the management study of the development of the Master of Islamic Studies Program at UIN Raden Fatah and other Islamic colleges. While practically, this research is expected to be useful and / or input for the development of a strategic plan for developing the Master of Islamic Studies Program at UIN Raden Fatah Palembang. This study is a field research with a descriptive approach, namely research that is limited to efforts to reveal a problem and the situation as it is, so that it is only a disclosure of facts by analyzing data.